2017
DOI: 10.2215/cjn.05670517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Novel MAGED2 Mutations in Antenatal Bartter Syndrome

Abstract: mutations explained 9% of cases of antenatal Bartter syndrome in a French cohort, and accounted for 38% of patients without other characterized mutations and for 44% of male probands of negative cases. Our study confirmed previously published data and showed that females can be affected. As a result, this gene must be included in the screening of the most severe clinical form of Bartter syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 20 publications
3
42
0
1
Order By: Relevance
“…55 In a French cohort, MAGE-D2 mutations explained 9% of antenatal BS cases. 56 In the same cohort, severe polyhydramnios occurred in all pregnancies and most patients had a weight and/or length above the 90th percentile. Plasma chloride is higher in patients with MAGE-D2 mutations compared with other antenatal BS and, together with birth weight percentile, contribute to differentiate the transient form.…”
Section: Transient Antenatal Bsmentioning
confidence: 85%
“…55 In a French cohort, MAGE-D2 mutations explained 9% of antenatal BS cases. 56 In the same cohort, severe polyhydramnios occurred in all pregnancies and most patients had a weight and/or length above the 90th percentile. Plasma chloride is higher in patients with MAGE-D2 mutations compared with other antenatal BS and, together with birth weight percentile, contribute to differentiate the transient form.…”
Section: Transient Antenatal Bsmentioning
confidence: 85%
“…In all babies that survived the neonatal period, BS was found to be transient. Interestingly, 2 of the reported patients were female: the severe phenotype could be explained by extremely skewed X-inactivation in 1 of them [43].…”
Section: New Insightsmentioning
confidence: 99%
“…Recently, Legrant et al reported 17 additional cases, including two females with type 5 BS. They reported additional clinical characteristics in their cohort, such as the gestational age at onset varying between 18 and 27 weeks or kidney function remaining normal in those with this genotype …”
Section: Subtypes Of Bs/gsmentioning
confidence: 99%